Real time power system harmonic distortion assessment virtual instrument - Tan R.H.G.; Ramachandaramurthy V.K. (2023)
This paper presents a real time power system harmonic distortion assessment instrument implemented using virtual instrument concept. The measurement hardware consists of measurement probes with signal conditioning circuit connected to a data acquisition module. The data acquisition module is interface to computer through a USB interface. Harmonic distortion assessment algorithm using Fourier transform was implemented using MATLAB. A graphical user interface was developed to display the harmonic distortion assessment in real time. The harmonic distortion is able assess individual harmonic order up to 50th order and the total harmonic distortion according to IEEE 519, IEC 61000-2-2 or EN 50160 standards selected by the user. An acceptability index is also proposed in this paper for trend assessment. The proposed real time harmonic distortion assessment virtual instrument was evaluated through field testing. The test results show promising performance for the proposed real time power system harmonic distortion assessment virtual instrument. 2012 IEEE.